TELAH HASIL PRODUKSI TANAMAN KELAPA SAWIT DENGAN PENERAPAN JALAN SELENDANG - Aditya, Aprisa; Madusari, Sylvia; Kuvaini , Aang (Universitas Djuanda, 2022)
Oil palm plants can be grown on flat, wavy, and hilly land with a land slope range of 0%-30%. The oil palm plantation area of PT ABC is 14.7 thousand Ha, with the landscape dominated by hilly topography. Conservation practice of the hilly regions in PT ABC is carried out by making contour roads and terraces. At PT ABC on five blocks in Division 1, block O, L, K, M, J was making a non-standard contour road. Therefore, these conditions cause decreases in production because the harvester has difficulty carrying fruit, and finally, the fruit is left behind. To overcome it, PT ABC opens the road (harvesting path) specifically for harvesting to resolve the problem. This research aims to determine the impact of harvesting path formation on oil palm production at PT ABC. The methodology of the study is by comparing data obtained from companies and analyzed descriptively in the field. The data collected are primary data and secondary data. The results showed that harvesting path formation influences oil palm production in PT ABC by increasing output by 21%-38% or increasing by an average of 1 ton/Ha/year.